IMPLEMENTATION OF EDUCATIONAL PARENTING PATTERNS BY BADUY PEOPLE - Hasmika, Hasmika; Malihah, Elly (Universitas Pendidikan Indonesia, 2020)
This study aims to describe the implementation of educational parenting patterns pf Baduy people, one of the indigenous people in Indonesia. The approach in this study is a qualitative approach administering documentation study or literacy to see or answer two problems in this study first, which is the implementation of parenting in education of the Baduy people. The results of this study showed that based on the historical facts, the Baduy tribe still upholds their customs in the interior of Banten Province in the Lebak Regency right in the Kanekes Village so that they cover themselves in formal education; however, for parenting in education, it turns out they still use customary methods in educating their children. The implementation of parenting in education was carried out in three ways, namely the implication of the adoption of parenting in education through the family environment, customary environment (Indigenous Leaders) and through peer learning.